The endurance of the modernist planning paradigm: the Functional City in contemporary planning in Medellķn, Colombia - Calderón, Edwar (Journal of Architecture and Urbanism, 2017)
The Functional City principles steered the development of Latin American cities post WWII, but their influence in current urbanisation in LA has not been acknowledged or studied, due to the presumption by planners that contemporary planning operates within a very different planning paradigm to the earlier modernist one. In contrast, this paper argues that contemporary urban planning practices in Colombia are still dependent today on functionalist urbanism. Through a case study of three of the 28 approved Planes Parciales (sectorial plans) in Medellin, Colombia, based on primary data sources, I argue how the Functional City principles have been overshadowed by and formulated from a socio-economic perspective which creates discrepancies between local planners and academics regarding their application. This study contributes to a better understanding of current urbanisation patterns in Latin America. Furthermore, this study will invite reflection and public debate over questions such as: urbanization for whom/against whom and who decides?